Critical fluctuations as an early warning signal of sports injuries? A proof of concept using football monitoring data - Neumann, N. D.; Brauers, J. J.; van Yperen, N. W.; van der Linde, M.; Lemmink, K. A. P. M.; Brink, M. S.; Hasselman, F.; den Hartigh, R. J. R. (Sports Medicine - Open, 2024)
Background There has been an increasing interest in the development and prevention of sports injuries from a complex dynamic systems perspective. From this perspective, injuries may occur following critical fluctuations in the psychophysiological state of an athlete. Our objective was to quantify these so-called Early Warning Signals (EWS) as a proof of concept to determine their explanatory performance for injuries. The sample consisted of 23 professional youth football (soccer) players. Self-reports of psychological and physiological factors as well as data from heart rate and GPS sensors were gathered on every training and match day over two competitive seasons, which resulted in an average of 339 observations per player (range = 155-430). We calculated the Dynamic Complexity (DC) index of these data, representing a metric of critical fluctuations. Next, we used this EWS to predict injuries (traumatic and overuse).